Safety, Tolerability, and Pharmacokinetics of ARC‐520 Injection, an RNA Interference‐Based Therapeutic for the Treatment of Chronic Hepatitis B Virus Infection, in Healthy Volunteers - Schluep, Thomas; Lickliter, Jason; Hamilton, James; Lewis, David L.; Lai, Ching‐Lung; Lau, Johnson YN; Locarnini, Stephen A.; Gish, Robert G.; Given, Bruce D. (Clinical pharmacology in drug development, 2017)
ARC‐520 Injection, an RNA interference drug for the treatment of hepatitis B that targets cccDNA‐derived viral mRNA transcripts with high specificity, effectively reduces the production of viral proteins and HBV DNA. In this phase 1 randomized, double‐blind, placebo‐controlled study, 54 healthy volunteers (half male, half female) received a single, intravenous dose of 0.01–4.0 mg/kg ARC‐520 Injection (n = 36) or placebo (n = 18). Assessments included safety, tolerability, pharmacokinetics, and pharmacodynamics (cytokines and complement). Pharmacokinetics of the siRNA and peptide excipient components contained in ARC‐520 Injection showed a relatively short half‐life of 3–5 and 8–10 hours, respectively. Dose exposure linearity was demonstrated within the dose range. ARC‐520 Injection was well tolerated, with adverse‐event frequency the same as placebo and no serious adverse events. ARC‐520 Injection was initially found to induce histamine release through mast cell degranulation, resulting in 2 moderate hypersensitivity reactions. However, after initiation of pretreatment with oral antihistamine, no further hypersensitivity reactions occurred. Low‐level, transient complement induction and sporadic, mild, and transient elevations of several cytokines were observed but not associated with any symptoms. ARC‐520 Injection showed a favorable tolerability profile in this single‐dose study in healthy volunteers. Oral antihistamine pretreatment is recommended in the future to offset mast cell degranulation stimulation.